Diversificação dos modos de ser masculino e estatização da violência masculina na escrita literária e jornalística de Bernardo Guimarães (1869-1872) - Matheus da Cruz e Zica (2011)
There are two main factors that stimulated us to investigate questions regarding education and masculinity in the XIX century: the lack of studies concerning this theme in the field of History of Education; and the consciousness that this lack of studies contributes to the continuity of male chauvinism, which has been responsible for tragic consequences to many Brazilian lives even nowadays. We worked, in this thesis, with the perspective that gender education would have at least two distinct particularities: it would be related not exclusively to one generation, as it makes part of the incomplete process of identitarian construction, comprising childhood, youth, adulthood and elderliness; and it would not take place nor particularly nor fundamentally at school, once the enormous flux of representations and cultural practices diffuses particular models of gender, which also contributes to define the identitarian constructions of individuals from different social contexts. Taking into consideration these premises, we decided to study the representations related to the masculine gender introduced primarily by Bernardo Guimarães literature, but also by other writers who were producing between 1869 and 1872, such as José de Alencar, Machado de Assis and Alfred Taunay which had a considerable influence on the choice of this specific period. Besides the novels, short-stories and poems written by those authors, other sources had also been researched, for instance, journals, official returns of the current Presidents of the Province of Minas Gerais during those years and travel reports. The intersection of this documental diversity enabled us to verify if there was any disparity in the manners how the masculine gender was treated in the period. It contributed not just to clarify the positions of each specific text concerning the changes in gender relations, already in process by those years, but also to exemplify some contradictions that seemed to determine that particular moment. Finally, the thesis sustains that the journalistic and literary works of Bernardo Guimarães, produced between 1869 and 1872, captured and contributed to the development of a process that could be modifying the current perceptions regarding gender subjects: 1) a diversification of the manners of being masculine; and 2) the statization of masculine violence. This argument was analyzed in the five chapters that compose the thesis.